Conceptual approach of shared decision making in physical therapy: An approach for betterment of patients? - Syed, Hamna; Zubaira, Kanwal; Tanoli, Anum Qayyum; Khalid, Saif Ullah (International Journal of Endorsing Health Science Research, 2019)
Background: Shared decision making (SDM) depicts the work that patients and clinicians do together to consider the relative benefits of accessible administration choices and choose an arrangement that fits the patient objectives, inclinations and setting. SDM decreases the authoritative control between the patient and physical therapist. SDM allows a balanced relationship between a clinician and patient. The practical application of evidence-based practice in health care is always been a challenge for clinician. The objective of this study was to explore the use of shared decision making among physical therapists in Karachi. Methodology: A cross-sectional study was conducted at the Institute of physical medicine and rehabilitation (IPM&R) department of Dow University of Health Sciences from 3 August 2017 till 13 April 2018. A total of 232 physiotherapists from different hospital and rehabilitation centers of Karachi participated in the study. SDM Q-Doc 9 (a physician version) questionnaire and questions regarding barriers were used to collect data. Those participants who fulfilled the inclusion criteria i.e. graduate physiotherapists and postgraduates and completed the entire survey were included in this study. Following participants were excluded undergraduate physical therapist (PT’s), house officers, internees, technicians, and academic staff of physiotherapy, non- practicing PT’s and other healthcare professionals. Data was analyzed by using SPSS version 20.00. Categorical variables were reported as frequency/percentage, while numerical data was presented as Mean±SD. Descriptive statistics test were applied. Results: The result showed that use of SDM was moderate (70.3%) among physiotherapists and the barriers included were: physician’s instructions (67.7%), lack of time (53.6%) and misconception of patient about disease or treatment (65.9%) which resisted in utilization of SDM. Conclusion: In conclusion we can state that the institutional physical therapists would prefer to use SDM moderately and it could be due to a relatively new concept.